Prevalence of Anemia among Children Diagnosed with Pneumonia Attending Birat Medical College Teaching Hospital, Morang, Nepal - Jha, Chandra Bhushan; Rimal, Hem Sagar; Subedi, Ram Bhakta (Birat Journal of Health Sciences, 2021)
Introduction: Childhood pneumonia is the leading cause of serious illness and death worldwide. In developing countries, pneumonia is the biggest single cause of childhood death under the age of 5 years. Globally, anemia is a major nutritional problem of immense public health significance. Iron deficiency anemia in children occurs most frequently between the age of 6 months and 3years, the same period of age when repeated infections occur.Objective: The main objective of this study is to determine the prevalence of anemia among children diagnosed with pneumonia.Methodology: This is a hospital based cross sectional study carried out in the Department of Paediatrics, Birat Medical College Teaching Hospital, from 15th February 2020 to 15th August 2020. This study was performed on 150 pneumonic children between 6 to 60 months of age. History regarding fever, cough and fast breathing was taken.  All the data were recorded in the preformed proforma. Data was analyzed using SPSS version 16.Results:  This study was performed on 150 pneumonic children, in which male babies (n=93; 62%) outnumbered the female babies (n=57; 38%). The majority of children were in the age group of 6 to 24 month (n=85; 56.7%). The mean hemoglobin level was 9. 49±1.39 gm/dl. The hemoglobin level less than 11 gm/dl was seen in 102 (68%) cases. Microcytic hypochromic anemia was present in 73 (71.6%) children.Conclusion: The prevalence of anemia among the pneumonic children of 6-60 months is 68% that is higher than the national data (52.6%) of prevalence of anemia in the same age group. While treating childhood pneumonia, checking hemoglobin on regular basis will be very useful to diagnose and manage concurrent anemia